2020
DOI: 10.1177/1471301220964393
|View full text |Cite
|
Sign up to set email alerts
|

Important aspects of home care service: An interview study of persons with dementia

Abstract: Background and Aim Because of the policy of ‘ageing in place’ and a decreasing number of beds in residential settings, more persons with dementia live at home with support from home care services. However, previous studies have revealed more unmet needs and a lower quality of life in this group than in other groups. Because few qualitative studies are performed in which persons with dementia have the opportunity to tell their own stories and describe what they find important, this study aimed to interview pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…A recent qualitative study showed a similar result, where persons with dementia expressed that having a relationship with those who came to their homes (ie, socialising with the staff and being seen as an integral part of society) were vital components of receiving home care service. 30 …”
Section: Discussionmentioning
confidence: 99%
“…A recent qualitative study showed a similar result, where persons with dementia expressed that having a relationship with those who came to their homes (ie, socialising with the staff and being seen as an integral part of society) were vital components of receiving home care service. 30 …”
Section: Discussionmentioning
confidence: 99%
“…Different approaches were found to intertwine in daily life and were dependent on individual, relational, and external factors. Other studies found that persons with dementia, in their early stages, can be capable of articulating what is important to them regarding their needs and preferences about both the content and the delivery of elder care services [28,29]. Persons with dementia were also found to be less satisfied with the decision-making process about elder care services compared to their carers [30], and they were unable to influence care decisions left to them due to a feeling of loss of control over their everyday life [31].…”
Section: Research On Care Decisions Involving Dementiamentioning
confidence: 99%
“…Remote treatment via at-home or community-based CCTs may increase accessibility and autonomy in the cognitive training of adults with MCI [20] . The importance of home-based support services has been increasingly highlighted, with the number studies on at-home and community center CCTs increasing [21] . However, further verification of the feedback mechanisms in treatments and the effects on cognitive functioning are required [22] .…”
Section: Introductionmentioning
confidence: 99%